A Scoping Review on the Methods Adopted and Rationale Applied for Therapeutic Administration of Ghee or Oil as a Purificatory Regimen - Manikandan, Divya; Basheer, Muhasina Manalilparambil; Thomas, Shitha; Mangampadath, Abhilash; Sukumaran, Seena (Asian Journal of Biological and Life Sciences)
Snehapana (therapeutic intake of ghee /oil) is a specific modality of treatment uniquely mentioned in Ayurveda. It involves the oral administration of medicated oil or ghee to attain specific therapeutic goals. Snehana therapy has a vital role in panchakarma. It is a procedure through which one can induce snigdhata (unctuousness) to the body. Snehapana can be conducted as purvakarma (prior to the main procedure) in sodhana (cleansing therapy), and it can also be customized as a pradhana karma (main therapeutic procedure) in specific conditions. The present review is an effort to understand the wide variety of snehapana in different medical conditions by analyzing articles published from 1984 to 2023. We have screened 115 articles of PUBMED, DHARA, and AYUSH RESEARCH PORTAL by using key words Snehapana, Sneha, Snehapan, Snehapaan, Fat and Ayurveda, and Lipids and Ayurveda and finally extracted 26 articles on sodhanartha snehapana. These articles were analyzed for the type of Sneha Dravya (fatty substance) used, methods, dosage, and duration in different medical conditions including neurological conditions, thyroid disorders, skin disorders, metabolic disorders, musculoskeletal disorders and some rare diseases. The most common dosage regimen employed is the Arohana matra (escalating dose) method, with a 7 days treatment duration. Significant variability in treatment protocols suggests consideration of individual patient factors and conditions.
Keywords: Arohana matra; Ghee or Oil; Scoping Review; Snehapana; Sodhanartha.